Sinorhizobium meliloti FcrX coordinates cell cycle and division during free-living growth and symbiosis by a ClpXP-dependent mechanism - Sara Dendene; Shuanghong Xue; Roza Mohammedi; Adam Vieillard; Quentin Nicoud; Odile Valette; Angela Frascella; Anna Bonnardel; Romain Le Bars; Mickaël Bourge; Peter Mergaert; Matteo Brilli; et al. (Proceedings of the National Academy of Sciences, 2025)
Sinorhizobium meliloti is a soil bacterium that establishes a nitrogen-fixing symbiosis within root nodules of legumes. In this symbiosis, S. meliloti undergoes a drastic cellular change leading to a terminally differentiated form, called bacteroid, characterized by genome endoreduplication, increased cell size, and high membrane permeability. Bacterial cell cycle (mis)regulation is at the heart of this differentiation process. In free-living cells, the master regulator CtrA ensures the progression of cell cycle by activating cell division (controlled by FtsZ) and inhibiting DNA replication, while on the other hand the so far poorly unknown downregulation of CtrA and FtsZ is essential for bacteroid differentiation. Here, we combine cell biology, biochemistry, and bacterial genetics to understand the functions of FcrX, a factor that controls both CtrA and FtsZ in free-living growth and in symbiosis. Depletion of the essential gene fcrX led to abnormally high levels of FtsZ and CtrA and minicell formation. Using multiple complementary techniques, we showed that FcrX may interact with FtsZ and CtrA. Moreover, fcrX transcription is directly controlled by CtrA itself and the FcrX protein displays a cell cycle-dependent pattern. We showed further that FcrX also binds the degradosome complex ClpXP and its adaptors CpdR1 and RcdA, and that CtrA degradation efficiency depends on FcrX. We further showed that, despite weak homology with FliJ-like proteins, only FcrX proteins from closely related species are able to complement S. meliloti fcrX function. Finally, deregulation of FcrX showed abnormal symbiotic behaviors in plants suggesting a putative role of this factor during bacteroid differentiation.